Building an effective model of intelligent entrepreneurship development in digital economy - Ostrovska, Halyna; Tsikh, Halyna; Strutynska, Iryna; Kinash, Iryna; Petukhova, Olga; Golovnya, Оlena; Shehynska, Natalia (My University, 2021)
This paper explores peculiarities in the formation and development of intelligent entrepreneurship as a new social phenomenon of national economies and the imperatives of its manifestation in the economic environment. The relationship between intelligent, informational, and innovative activities that shape the environment of modern entrepreneurship has been established. A new understanding of the essence of “intelligent entrepreneurship” and “talent management” categories has been proposed. The value of human capital, the realization of intelligent capabilities of the individual is recognized as the basic value of intelligent entrepreneurship. It has been proven that in modern conditions the most promising for national economies is the transition to open innovation models. It is noted that the development and effective use of intelligent potential are due to the need to increase the efficiency of innovation, science, and education systems, which ensures the economic growth of the national economy. The structure of intelligent potential of entrepreneurship under the conditions of digital transformation of the economy has been built. Original views on the essence and significance of the talent management system are presented. It is noted that intelligent entrepreneurship requires a holistic approach. The classification of communities of intelligent practitioners has been devised. The system of management of advanced reproduction of the latest knowledge of business entities has been formed. The directions of digital transformation of intelligent entrepreneurship have been outlined. A system-integrated methodological approach to determining the Index of digital transformation of business entities has been devised. The study results build on the theoretical and practical aspects of intelligent entrepreneurship, contribute to the effective use and development of the intelligent potential of entrepreneurial organizations and their network associations.
Keywords: digital economy; intelligent entrepreneurship; knowledge management; intelligent commerce; digital transformation; цифрова економіка; інтелект підприємництво; управління знаннями; розумна комерція; цифрова трансформація; кафедра маркетингу